Preparation and Characterization of ZnO and TiO2 Sol-Gel Thin Films Deposited by Dip Coating (Hungarian Journal of Industry and Chemistry, 2009)
ZnO and TiO2 thin films were prepared by sol-gel technique. Dip coating was applied for film deposition and withdrawal velocity was varied in order to control the film thickness. The deposited films were annealed to remove additives and obtain oxide layers. Large silicon and glass substrates were coated with homogeneous, reflective semiconductor layers of different refractive index values. UV-Vis spectroscopy and scanning angle reflectometry measurements were performed to determine refractive index and thickness values. The using of different stabilizers for ZnO precursor sol preparation resulted in different layer thicknesses and very different response to the varying of the withdrawal speed. According to photoluminescence measurements ZnO films are of good crystallinity. Thicknesses of deposited films were found to be in the range of 6-200 nm. TiO2 coatings show strong interference colours due to their high refractive index.